Nepal Systematic Country Diagnostic : A New Approach to a Federal Nepal - World Bank Group (World Bank, Washington, DC, 2018)
This systematic country diagnostic (SCD) examines the key constraints to and opportunities for accelerating poverty reduction and enhancing shared prosperity in Nepal. The SCD builds on a broad body of analytical work conducted in Nepal, but particularly on three World Bank reports published in 2017: moving up the ladder: poverty reduction in Nepal, climbing higher: toward a middle-income Nepal, and the Nepal risk and resilience assessment. It also builds on evidence compiled in six working groups and consultations and surveys in all seven Nepalese provinces with civil society organizations, the private sector, government, development partners, and citizens. The SCD highlighted key knowledge gaps. The key knowledge gaps include: (a) poverty trends since the earthquake, blockade, and slowdown of remittances; (b) how best to increase the accountability and strengthen the capacity of local governments; (c) the impact of lack of competition in specific sectors on job creation, prices, and welfare; (d) the potential for reducing environmental vulnerability through investments and of what type; (e) the political economy of multiple ministries in natural resource management and how to encourage consolidation; (f) which interventions are most effective to reduce malnutrition in different parts of the country; and (g) how to make the cost of migration more affordable for poor households.